ANALISIS HUBUNGAN SEMANGAT KERJA DENGAN KINERJA DI BADAN KESATUAN BANGSA, POLITIK DAN PERLINDUNGAN MASYARAKAT KABUPATEN KAPUAS - Abdul Haliq; Umar Makawi; Dewi Merdayanty (AS-SIYASAH: Jurnal Ilmu Sosial Dan Ilmu Politik, 2016)
The objective of this research is to know the work enthusiasm and performances employee, the relationship with the characteristics of the gender, age, education, and year of service, and to know correlation work enthusiasm with performances employee at Badan Kesatuan Bangsa, Politik dan Perlindungan Masyarakat Kabupaten Kapuas. The method used is a quantitative research approach and the instrument is a questionnaire that analyzed by using Chi Square Goodness Of Fit Test, Independent Test, and Person Correlation. The research result show that work enthusiasm are not spread in the all category, but more is pretty good category (43,6%), so as performances employee is pretty good category (46,2%). In addition, there is not any relationship among the characteristics of gender, age, education, dan year of service with work enthusiasm and performances employee. The other result there is a correlation significant work enthusiasm with performances employee, and the correlation strong enough category.